Dissolution of Soap Scum by Surfactants. Part III. Effect of Chelant Type on Equilibrium Solubility and Dissolution Rate of Calcium and Magnesium Soap Scums in Various Surfactant Systems. Issue 6 (25th September 2015) - Itsadanont, Sawwalak; Theptat, Prariyada; Scamehorn, John F.; Soontravanich, Sukhwan; Sabatini, David A.; Chavadej, Sumaeth
Abstract: Soap scum can be effectively removed by using an appropriate surfactant with a chelating agent at a high solution pH. The equilibrium solubilities and dissolution rates of two model soap scums [calcium stearate and magnesium stearate: Ca(C18 )2 and Mg(C18 )2 ] were investigated in aqueous solutions containing three different types of surfactants [methyl ester sulfonate (MES) as an anionic surfactant; alcohol ethoxylate (EO9) as a nonionic surfactant; and dimethyldodecylamine oxide (DDAO) as an amphoteric surfactant] in the presence of different biodegradable chelants: trisodium ethylenediamine disuccinic acid (Na3 EDDS) and tetrasodium glutamate diacetic acid (Na4 GLDA) compared with disodium ethylenediamine tetraacetate (Na2 EDTA), a chelant with poor biodegradability. The highest equilibrium solubility and dissolution rate of either soap scum were observed at high pH in the DDAO system with Na4 GLDA. In addition, the calcium soap scum had a similar to higher equilibrium solubility and a higher dissolution rate constant as compared with the magnesium soap scum.